Nitric oxide in the regulation of fruit ripening: Challenges and thrusts - Singh, Zora; Khan, Ahmad; Zhu, S.; Payne, Alan (Postharvest solution, 2013)
Purpose of review: Nitric oxide (NO) is a multifunctional biomolecule involved in a variety of biological plant functions such as stomatal movement, plant respiration, germination of seeds, cell differentiation and fruit ripening. This article focuses on the role of NO in the regulation of fruit ripening. Findings: Recent reports suggest that optimum NO levels: (1) delay the climacteric phase of many tropical fruits; (2) prolong the postharvest storage life of a wide range of horticultural crops by impeding ripening and senescence; (3) exhibit antagonistic interaction with ethylene, with the ability to suppress the biosynthesis of ethylene by suppressing the activities of ethylene synthesis enzymes; (4) reduce ethylene production, and consequently, delays fruit ripening, with reduction in fruit softening and delaying the metabolism of sugars and acids; (5) protect various fruit from a wide range of phytopathogens during postharvest storage. Directions for future research: There is a need to investigate the volatile nature of NO and reactive oxygen species toxicity at certain super optimal concentrations; the precise monitoring of their threshold levels is very important for maintaining the desired beneficial levels needed for the modulation of fruit ripening. The development of effective and precise NO delivery systems offers an attractive opportunity to harness the beneficial effects of NO in the regulation of fruit ripening, extending postharvest life and maintaining the quality of horticultural produce.